2017
DOI: 10.1200/jco.2016.71.9476
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Trial of Atezolizumab As First-Line or Subsequent Therapy for Patients With Programmed Death-Ligand 1–Selected Advanced Non–Small-Cell Lung Cancer (BIRCH)

Abstract: Purpose BIRCH was designed to examine the efficacy of atezolizumab, a humanized anti-programmed death-ligand 1 (PD-L1) monoclonal antibody, in advanced non-small-cell lung cancer (NSCLC) across lines of therapy. Patients were selected on the basis of PD-L1 expression on tumor cells (TC) or tumor-infiltrating immune cells (IC). Patients and Methods Eligible patients had advanced-stage NSCLC, no CNS metastases, and zero to two or more lines of prior chemotherapy. Patients whose tumors expressed PD-L1 using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
295
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(309 citation statements)
references
References 26 publications
12
295
0
2
Order By: Relevance
“…This has been confirmed in a recent meta-analysis [78] and corroborated in other studies [79]. In the BIRCH trial, ORRs were lower in previously-treated EGFR mutant-positive patients treated with atezolizumab compared with EGFRwild-type patients [42]. In the JAVELIN solid tumor trial, no confirmed responses to avelumab were reported in patients (n = 10) with EGFR mutations or ALK translocations [45].…”
Section: Mutational Status Egfr and Alksupporting
confidence: 54%
See 1 more Smart Citation
“…This has been confirmed in a recent meta-analysis [78] and corroborated in other studies [79]. In the BIRCH trial, ORRs were lower in previously-treated EGFR mutant-positive patients treated with atezolizumab compared with EGFRwild-type patients [42]. In the JAVELIN solid tumor trial, no confirmed responses to avelumab were reported in patients (n = 10) with EGFR mutations or ALK translocations [45].…”
Section: Mutational Status Egfr and Alksupporting
confidence: 54%
“…Following positive results in two Phase II trials (POPLAR and BIRCH) [42,43], atezolizumab was compared with docetaxel in a Phase III study (OAK) in unselected patients who had received up to two previous chemotherapy regimens, including at least one platinum-based therapy. OS was significantly improved in the atezolizumab treatment group compared with the docetaxel group.…”
Section: Pd-l1 Inhibitorsmentioning
confidence: 99%
“…Peters and colleagues[30, 31] have recently reported the results of the “BIRCH” study, a phase II single-arm trial of atezolizumab as first-line or subsequent therapy for locally advanced or metastatic PD-L1-selected NSCLC. Patients with PD-L1 positive tumors (TC2/3 and/or IC2/3) and without brain metastasis were eligible.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16]. These studies have established PD-1/PD-L1 pathway blockade as a powerful new line of therapy for patients with advanced NSCLC following progression after platinum-based therapy [9,11].…”
mentioning
confidence: 99%